High Prevalence of Serum Immunoglobulin G Antibody to Helicobacter pylori and Raised Serum Gastrin and Pepsinogen Levels in Enlarged Fold Gastritis - Yuichi Yasunaga; Juan José Bonilla-Palacios; Yasuhisa Shinomura; Shuji Kanayama; Yoshiji Miyazaki; Yuji Matsuzawa (Canadian Journal of Gastroenterology)
To clarify the prevalence of Helicobacter pylori infection in enlarged fold gastritis, serum immunoglobulin (Ig) G antibody to H pylori was determined in 19 patients with severely enlarged gastric body folds (the widest fold greater than 10 mm on the radiograph), 55 patients with moderately enlarged folds (6 to 10 mm) and 44 control subjects (5 mm or less). The prevalence of serum IgG antibody to H pylori in the severe (100%) and moderate groups (100%) was significantly higher than that in controls (34.1%) (PÃ0.01). There were significant differences among the three groups in serum gastrin, pepsinogen I and pepsinogen II levels (severe had the highest levels, followed by moderate and then controls, PÃ0.001). H pylori colonization in the gastric mucosa was confirmed by culture, urease test or both, and inflammation by hematoxylin and eosin stain in the 25 H pylori seropositive patients who underwent endoscopy and biopsy. Results suggest that H pylori infection is highly prevalent in enlarged fold gastritis. Further studies on enlarged fold gastritis and H pylori infection are needed.